Identification of Capsid/Coat Related Protein Folds and Their Utility for Virus Classification - Nasir, Arshan; Caetano-Anollés, Gustavo (Frontiers in Microbiology, 2017)
The viral supergroup includes the entire collection of known and unknown viruses that roam our planet and infect cellular life forms. The supergroup is remarkably diverse both in its genetics and morphology and has historically remained difficult to study and classify. The accumulation of protein structure data in the past few years now provides an excellent opportunity to re-examine the classification and evolution of viruses. Here we scan completely sequenced viral proteomes from all genome types and identify protein folds involved in the formation of viral capsids and virion architectures. Viruses encoding similar capsid/coat related folds were pooled into lineages, after benchmarking against published literature. Remarkably, the in silico exercise reproduced all previously described members of known structure-based viral lineages, along with several proposals for new additions, suggesting it could be a useful supplement to experimental approaches and to aid qualitative assessment of viral diversity in metagenome samples.